Moodle 1. 9 math : integrate interactive math presentations, incorporate Flash games, build feature-rich quizzes, set online tests, and monitor student progress using the Moodle e-learning platform /: integrate interactive math presentations, incorporate Flash games, build feature-rich quizzes, set online tests, and monitor student progress using the Moodle e-learning platform. (©2009) - Unknown
No abstract available